Patent Protection for Artificial Intelligence as Computer-Implemented Inventions Between Indonesia and Japan - Rumahorbo, Veni Theresya Fortuna; Evi; Januardy, Ivans (GoAcademica Research & Publishing, 2025)
The development of artificial intelligence (AI) technology has had a significant impact on various sectors, including industry, health, and education. AI not only improves operational efficiency but also creates innovations that change human interaction with technology. In this context, protecting intellectual property rights, especially patent rights, is very important to encourage innovation and investment. This study discusses the challenges and opportunities faced by Indonesia in formulating patent protection regulations for AI-based inventions and compares them with the more comprehensive legal framework in Japan. Although Law Number 13 of 2016 in Indonesia provides a legal basis for patent protection, there is still legal uncertainty and a lack of specific regulations regarding AI inventions. In contrast, Japan has developed clear guidelines from the Japan Patent Office (JPO) that support patent protection for AI technology. This study suggests that Indonesia needs to formulate more specific and comprehensive regulations to improve intellectual property rights protection in the AI ​​sector. By adopting best practices from Japan, it is hoped that Indonesia can encourage more investment and innovation in the field of artificial intelligence, which in turn will contribute to economic growth and national competitiveness.